Yield components in new pear cultivars and breeding forms in the Middle Urals - G. N. Tarasova (Труды по прикладной ботанике, генетике и селекции)
Sverdlovsk Horticultural Breeding Station specializes in the development of fruit and berry cultivars for the Middle Urals. One of its tasks is pear breeding for high winter-hardiness, high yield, and good fruit quality. Ten new pear cultivars and improved forms of local breeding were selected as the material for this study versus the reference cultivars ‘Talitsa’, ripening in summer, and ‘Berezhenaya’, ripening in late autumn. Observations were conducted across the decade of 2009–2019. The cultivars ‘Letnyaya zolotistaya’, ‘Chusovaya’, ‘Berezhenaya’ (ref.), ‘Sultan’, and breeding form DL-33-307 were found to possess resistance of flowers to late spring frosts. Cvs. ‘Letnyaya zolotistaya’, ‘Berezhenaya’ (ref.) and ‘Sultan’ were early-fruiting; cvs. ‘Talitsa’ (ref.) and ‘Chusovaya’, breeding forms ZS-IV-5-11, DL-33-307, DL-II-31n-207, ZS-II-15-18 and ZS-IV-5-19 were mid-fruiting; breeding form ZS-IV-15-38, late-fruiting. An early onset of full fructification at the age of 10–11 years or more, combined with high yield at the same age, was observed in cvs. ‘Berezhenaya’ (ref.), ‘Sultan’, ‘Letnyaya zolotistaya’, and breeding form ZS-II-15-18. New cultivars ‘Letnyaya zolotistaya’ and ‘Sultan’ were highlighted for a combination of valuable traits: earliness, high yield, and high growth rates in the plantlet stage. Cv. ‘Letnyaya zolotistaya’ had attractive good-tasting fruits, weighing 76 g, ripening in summer. Cv. ‘Sultan’ yielded nicelooking and good-tasting fruits, weighing 129 g, ripening in winter. Cv. ‘Chusovaya’ was identified for its nice-looking fruits with a very good taste.